Critical experimental issues of cracked aluminum beam in operational modal analysis / M. Azhan Anuar ... [et al.] - Anuar, M. Azhan; Mat Isa, A.A; A.R., Zamri (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Obtaining good experimental modal data in order to use it for further analysis is very essential in modal analysis. This paper investigates the dynamic characteristics of aluminium beam with a single crack at its centre using various identification algorithms in Operational Modal Analysis (OMA, or also called Output-Only or Ambient Modal Analysis). Algorithms such as Frequency Domain Decomposition (FDD), Enhanced Frequency Domain Decomposition (EFDD) and Stochastic Subspace Identification (SSI) are applied in this study. For its simplicity and direct investigation purpose, the beam considered is a free-free end beam condition. Comparison of the results of these techniques will be shown to justify the validity of each technique used. Good modal data are obtained by examining and emphasizing on technical aspects in processing the experimental data which are critical issues to be addressed. The accuracy of the results is duly examined for each post-processing modification made